ANALISIS KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA MAKASSAR - ST. Salmah ST. Salmah (AkMen JURNAL ILMIAH, 2013)
This study aims to determine the level of tax receipts restaurant , restaurant tax contributions to the Local Revenue in Makassar during the last five years (2009-2012). To obtain complete data in this study used data collection techniques appropriate to the circumstances or the nature of this type of research . In order to obtain accurate data , the data collection techniques used in this study is the observation , documentation and interviews. Tax revenue in the Revenue Office restaurant in Makassar fluctuate , restaurant tax developments in 2009 to 2012 are likely to increase or an increase of 19.30 percent . Local Revenue fluctuates in Makassar this is due to the presence of multiple sources of local tax revenue that fluctuates one of which is a restaurant tax revenue . Restaurant tax revenues in the period of 4 years in 2009 to 2012 contributed to the Local Revenue in Makassar with an average of 12.12 percent annually .